Knowledge organisation in institutional repositories: a case study on policies and procedures manuals in the Ibero-American environment - Bueno de la Fuente, Gema; Agustín-Lacruz, Carmen; Fujita, Mariângela Spotti Lopes [UNESP]; Terra, Ana Lúcia (Emerald, 2023)
Purpose: The purpose of this study is to analyse the recommendations on knowledge organisation from guidelines, policies and procedure manuals of a sample of institutional repositories and networks within the Latin American area and observe the level of follow-up of international guidelines. Design/methodology/approach: Presented is an exploratory and descriptive study of repositories’ professional documents. This study comprised four steps: definition of convenience sample; development of data codebook; coding of data; and analysis of data and conclusions drawing. The convenience sample includes representative sources at three levels: local institutional repositories, national aggregators and international network and aggregators. The codebook gathers information from the repositories’ sample, such as institutional rules and procedure manuals openly available, or recommendations on the use of controlled vocabularies. Findings: The results indicate that at the local repository level, the use of controlled vocabularies is not regulated, leaving the choice of terms to the authors’ discretion. It results in a set of unstructured keywords, not standardised terms, mixing subject terms with other authorities on persons, institutions or places. National aggregators do not regulate these issues either and limit to pointing to international guidelines and policies, which simply recommend the use of controlled vocabularies, using URIs to facilitate interoperability. Originality/value: The originality of this study lies in identifying how the principles of knowledge organisation are effectively applied by institutional repositories, at local, national and international levels.
Keywords: Academic repositories; COAR; Guidelines; Institutional repositories; Knowledge organisation; LA Referencia; Oasisbr; OpenAIRE; Policies; Procedure manuals; RCAAP; Recolecta